PEMIKIRAN SUFISTIK SAID NURSI - Damanik, Agusman (Jurnal Ushuluddin, 2018)
Said Nursi, one of the foremost Turki’s thought in the 20th century who had watched the divergence cause of the material progress which to ward to the secular thinking and acting. In concerning of Said Nursi on this case supported him to write monumental creation of Al-Nur treatise as the way to save the Moslem confidence. One of the discussion in the creation of Al-Nur which was presented by Said Nursi was Sufism law, that was the spiritual to know well of Allah by doing His doctrines and His Prophet doctrines which are depended on Al-Qur’an and Hadits. It is of course has a difference with the Sufism which is formulated by the Sufist leader. The student. The Sufism which was depended by Said Nursi could be the solution for the disappointment of modern human spiritual.